Miasta w dobie wyzwań zmieniającego się klimatu - Brzeziński, Kamil; Jurczak, Tomasz; Rzeńca, Agnieszka; Agnieszka Gralak (Public participation in urban climate policy making: The example of Lodz, 2024)
Cities are the largest contributors to pollution, which ultimately leads to climate change on a global scale. The negative, environmental, effects of cities are becoming so acute that they are mobilizing local authorities, but also citizens themselves, to take active measures. Sustainable urban development is becoming a necessity and requires the implementation of innovative instruments and solutions and the creation of an urban climate policy. An extensive review of the literature on the subject and a search of key international and national documents made it possible to outline a broad perspective on the conditions and determinants of contemporary urban development in the era of challenges caused by climate change.